Social interactions among research stakeholders and ethical issues in the context of community engagement in Malawi - Nyirenda, Deborah (2021)
This thesis examines community engagement practices and consequent effects on ethical research, knowledge re-production and study acceptability. Community engagement is promoted in international ethical guidelines for health research to engage communities in research design. Limited evidence exists on practical translation of these international ethical guidelines to improve ethical research. This study was undertaken to address this knowledge gap by using three ethnographic case studies in Malawi. A qualitative research design was used to understand community engagement practices in light of a theoretical framework of neo-colonial research relations. Three research projects were purposively selected as ethnographic case studies focusing on an urban, rural and hospital setting. I used participant observation to understand unarticulated aspects of community engagement. Field notes from participant observation were triangulated with 43 in-depth interviews and 17 FGDs with community leaders, research staff, community members and research participants. Thematic analysis was used to analyse and interpret findings by applying theories of neo-colonial research relations. Although international ethical guidelines promoted active involvement of communities in research design, neither researchers nor community members wished to engage in fully collaborative partnerships. Community engagement processes were shaped by historical experiences with service providers, political context, power dynamics between research stakeholders as well as social norms of interacting with outsiders. In addition, the broader socio-economic context and local power structures raised issues of structural coercion. Rather than improving ethical research practice, community engagement often influenced research participation and did not yield mutual benefits. Lack of community awareness of ethical guidelines or activism for collaborative partnerships affected successful translation of collaborative partnerships. These results raise important questions on how community engagement in low resource settings ought to balance between bridging research stakeholders’ contradictory expectations.